PENGARUH PENGAWASAN TERHADAP EFEKTIVITAS PENGGUNAAN DANA HIBAH PETERNAKAN DAN PERIKANAN (Studi Pada Dinas Peternakan dan Perikanan Kabupaten Bandung Barat) - Asep Suhendi Arifin (LPPM UNSAP & FISIP UNSAP, 2017)
This research is motivated by the lack of effectiveness in the use of grants Livestock and Fisheries of West Bandung regency. The problem is assumed to be affected by not optimal supervision conducted by the Department of Animal Husbandry and Fishery West Bandung regency. Based on these problems, we propose the problem: